Towns and cities energy consumption: case of Kano metropolis Nigeria - Abdullahi, Hashim; Asmawi, M. Zainora; Abdul Aziz, Abdul Razak (Science China Press, 2023)
Rapid population growth in the Kano metropolis of Nigeria and its consequential high energy consumption and carbon emission required mitigations. The study focuses on the energy consumption of built-up areas within the Kano metropolis of Nigeria towards low-energy carbon society development. Four hundred questionnaires were used, and geographical information system (GIS) was employed for locational map production, while descriptive statistics were employed for data analysis and presentation. The results indicate that low-income earners depend on wood fuel and charcoal as energy sources while middle-income earners used charcoal, kerosene, and electricity as energy sources. Additionally, high-income earners utilize electricity, diesel, and LPG. The results also depict that technology, weather conditions, and human sociology contribute to energy consumption and carbon emission across the world. The study demonstrates a strong need for energy low-carbon framework development for the Kano metropolis of Nigeria.